Barriers and drivers of Human-Centered ICT design: the missing elements in Malaysia - Hussein, Idyawati; Abu Seman, Esmadi Abu; Mahmud, Murni (INTAN, 2009)
Given the widely recognized importance of information and communication technology (ICT) for the successful government initiatives and business achievement; this study explored the perception of ICT-related officials and major stakeholder's group towards the barriers and drivers of human-centered technology development. The findings found that although Malaysia has successfully implemented ICT, issues of Human Computer Interaction (HCI) have not been distinct as they should be; there is a lack of study on the usability of ICT/ multimedia applications and less emphasis on adoption of designing interactive systems to support people and for the people to enjoy. Findings of this study indicate that human-centered barriers are clustered around the existing traditional bureaucratic system. In fact, different challenges related to the traditional model of bureaucracy such as mindset, institutional and managerial processes are considered as heart of all other barriers which have building block human-centered design. Interestingly, incentives for modernising and reinventing the government by using ICT with the intention of building citizen-centric, transparent and accountable and efficient government are placed at the core of driving forces for moving towards human-centered activities.